Future perspectives of therapeutic monoclonal antibodies development: new formats and new functions - Stojić-Vukanić, Zorica (Archives of Pharmacy, 2022)
Monoclonal antibody therapeutics have dramatically changed the landscape of medicine and human health. In 2022, thirty-six years on from the approval of a first monoclonal antibody, about 100 monoclonal antibodies for treatment of cancer and noncancer indications had secured United States Food and Drug Administration approval. The idea that antibodies could serve as therapeutics emerged over century ago, but it became a reality when scientists developed hybridoma technology for antibody generation in the laboratory. To avoid the shortcomings of the earliest therapeutic monoclonal antibodies of murine origin, which tended to be immunogenic in humans, therapeutic antibody constructs that were more human-compatible (chimeric and humanized) have been produced using genetic engineering technology. Finally, development of phage display, the human antibody mouse, and single B cell antibody innovative technologies, have enabled production of fully human therapeutic antibodies. The successful application of full-size monoclonal antibodies over the last decades has motivated the pharmaceutical company to develop various types of antibody formats in order to improve their efficacy and lower adverse effects. By using strategies to miniaturize and multifunctionalize antibody molecules new classes of antibody therapeutics, such as antibody derivatives (e.g., antibody–drug conjugates and immunocytokines), bispecific/multispecific antibodies, antibody fragments, were developed. In the future, with the progress of modern biotechnology, it can be expected that these new-designed antibodies will finally pave the way for successful treatments of various diseases.